2018
DOI: 10.21776/ub.jkb.2018.030.01.3
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Antosianin Ubi Ungu terhadap TNF-α, Apoptosis dan Memori Spasial Hipokampus Tikus Model Diabetes Melitus

Abstract: <p>Hiperglikemia pada diabetes melitus menyebabkan penurunan fungsi memori spasial. Terapi yang efektif terhadap gangguan fungsi kognitif akibat hiperglikemia yang sampai saat ini masih dalam perdebatan, menjadikan pendekatan pencegahan menjadi pilihan. Ubi ungu (Ipomoea batatas L.) merupakan tanaman tradisional yang mengandung antosianin, sebagai antiinflamasi, antioksidan, berhubungan dengan peningkatan signalling neuronal otak dalam memperbaiki fungsi memori. Tujuan dari penelitian ini adalah untuk me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…38 Studies conducted by Darwatik et al and Prabawati et al showed that diabetic rats had significantly different mean travel time with healthy controls after the diabetic group rats were given hyperglycemia exposure for 6 weeks, 2 weeks longer than the current study. 27,28 There is currently no ideal time reference for exposure to hyperglycemia in diabetic rats that can significantly influence the cognitive function of these experimental animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Studies conducted by Darwatik et al and Prabawati et al showed that diabetic rats had significantly different mean travel time with healthy controls after the diabetic group rats were given hyperglycemia exposure for 6 weeks, 2 weeks longer than the current study. 27,28 There is currently no ideal time reference for exposure to hyperglycemia in diabetic rats that can significantly influence the cognitive function of these experimental animals.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, these technical difficulties can be overcome by replacing this parameter with another one, called travel time, which measure the time taken by the rat when starting to swim until it reach the platform. 27,28 This study aims to investigate the effect of GLUT4 expression on hippocampal neurons on the spatial memory of Rattus novergicus rats induced diabetes by injection of streptozotocin and nicotinamide. This was our effort to prove the role of GLUT4 in the pathomechanism of diabetes-associated cognitive decline.…”
Section: Research Article Open Accessmentioning
confidence: 99%